Treatment Beliefs of Children and Adolescents With Chronic Diseases: Development of the Rehabilitation Treatment Beliefs Questionnaire for Children and Adolescents. (15th April 2022) - Metzner, Gloria; Höhn, Cindy; Nau, Anne; Sehlbrede, Matthias; Waldeck, Edith; Glattacker, Manuela
Abstract: Objective: Rehabilitation is an important component in the health care of children and adolescents with chronic diseases and aims at supporting patients' self-regulation for dealing with the disease. Patients' beliefs about illness and treatment are core elements in the self-regulation process. While questionnaires measuring illness beliefs for children and adolescents exist, questionnaires about their rehabilitation-related treatment beliefs are lacking. We therefore developed a questionnaire to assess the rehabilitation-related treatment beliefs of children and adolescents with chronic diseases (Rehabilitation Treatment Beliefs Questionnaire, RTBQ) and tested its psychometric properties. Methods: Ahead of their rehabilitation, children and adolescents, aged 12–17 years, answered 129 items, which were developed based on previous qualitative findings exploring children and adolescents' rehabilitation-related treatment beliefs. Psychometric testing included item analyses, exploratory factor analysis, internal consistency and bivariate correlations of the extracted scales, and the discriminatory power and difficulty of the final items. Results: The sample consisted of 170 participants with a mean age of 14.3 years ( SD = 1.6); 53.5% were female. After item analyses, 47 items remained for the exploratory factor analysis which revealed 22 items allocated to 4 scales: "expectations of communication and interaction, " "expectations of the treatment process, " "expectations of treatment success and sustainability, " and "expectations of one's own role in the rehabilitation process." The psychometric properties were acceptable to good. Conclusions: The RTBQ assesses various dimensions of rehabilitation-related treatment beliefs of children and adolescents with chronic diseases. While first psychometric results are promising, further psychometric testing is needed.